Front line extremity and orthopaedic surgery a practical guide - Bone, Lawrence B.; Mamczak, Christiaan N. (Springer, 2014)
This book, written by surgeons with experience in combat casualty care, will be relevant to all physicians working in forward surgical teams, combat surgical hospitals, or the "Charlie Med".